PROVIDING QUALITY EDUCATION IN THE PROCESS OF IMPROVING THE QUALITY AND EFFICIENCY OF EDUCATION - THE REQUIREMENT OF THE TIME (American Journal of Interdisciplinary Research and Development, 2023)
Through this article, we will refer to the social resources about the gradual application of the principles of individualization to the educational process, the improvement of teaching methods, the legal basis for improving the quality of educational services for children with disabilities, and the specific aspects of creating an inclusive educational environment. can be had.